UiO-66-(SH) 2 as stable, selective and regenerable adsorbent for the removal of mercury from water under environmentally-relevant conditions - Leus, Karen; Perez, Jeffrey Paulo H; Folens, Karel; Meledina, Maria; Van Tendeloo, Gustaaf; Du Laing, Gijs; Van Der Voort, Pascal (Faraday discussions, 2017)
The dithiol functionalized UiO-66-(SH) is developed as an efficient adsorbent for the removal of mercury in aqueous media. Important parameters for the application of MOFs in real-life circumstances include: stability and recyclability of the adsorbents, selectivity for the targeted Hg species in the presence of much higher concentrations of interfering species, and ability to purify wastewater below international environmental limits within a short time. We show that UiO-66-(SH) meets all these criteria.